2023
DOI: 10.3847/psj/aceefa
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Magnesium Sulfate Hydrate as a Potential Mechanism for Preservation of Microbial Viability on Europa

Ceth W. Parker,
Tuan H. Vu,
Taewoo Kim
et al.

Abstract: Europa's subsurface ocean is postulated to contain appreciable amounts of Mg2+ and SO 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Observations by Dawn have found that these deposits are made of salt minerals that are consistent with aqueous alteration of chondritic materials (such as sodium carbonate, ammonium bicarbonate/chloride, and hydrohalite) and are likely formed from the extrusion of briny water through fractures created by impacts and/or cryovolcanism. The discovery of salts holds important implications for Ceres’ astrobiological potential, since they have been known to be an effective medium for encapsulating extraterrestrial organic matter (e.g., inside meteoritic clasts), as well as preserving the viability of microorganisms under simulated ocean world environments …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations by Dawn have found that these deposits are made of salt minerals that are consistent with aqueous alteration of chondritic materials (such as sodium carbonate, ammonium bicarbonate/chloride, and hydrohalite) and are likely formed from the extrusion of briny water through fractures created by impacts and/or cryovolcanism. The discovery of salts holds important implications for Ceres’ astrobiological potential, since they have been known to be an effective medium for encapsulating extraterrestrial organic matter (e.g., inside meteoritic clasts), as well as preserving the viability of microorganisms under simulated ocean world environments …”
Section: Introductionmentioning
confidence: 99%
“…The discovery of salts holds important implications for Ceres' astrobiological potential, since they have been known to be an effective medium for encapsulating extraterrestrial organic matter (e.g., inside meteoritic clasts), 6 as well as preserving the viability of microorganisms under simulated ocean world environments. 7 In recent years, data returned by the Visible and Infrared (VIR) mapping spectrometer onboard the Dawn spacecraft have also revealed the presence of localized organic-rich areas on Ceres' surface. These were first detected 8 in the regions around the large Ernutet crater in the northern hemisphere, spreading over hundreds of square kilometers with an estimated abundance of ∼5 to 15 vol % depending on the end-members used for spectral modeling.…”
Section: Introductionmentioning
confidence: 99%